COMPARISON OF TRANSVERSE BODY SIZE BETWEEN HEALTHY AND PATIENTS WITH ACNE YOUNG BOYS AND GIRLS OF PODILLIA - Маєвський, О.Є.; Макарчук, І.М. (World of Medicine and Biology, 2014)
This article describes the differences between the covering body size in healthy and diseased with acne boys or girls common groups and mesomorphic somatotype. Proved that almost all studied dimensions are more important in patients with acne boys and girls compared to healthy researched of similar sex. Established gender differences in covering body size for most parameters - larger in healthy and patients with acne boys.